Post-operative adaptation of people with ostomy with and without complication: comparative study. - de Andrade Peixoto, Hugo; Sumas da Silva, Priscila Maria; Alfradique de Souza, Priscilla; Albuquerque Guimarães, Nathalia de Paula; Silva Pinto, Ana Cristina (UERJ Nursing Journal / Revista Enfermagem UERJ, 2021)
Objective: to analyze postoperative adaptations by people with intestinal elimination ostomies, with and without complications, using the Elimination Ostomy Adaptation Scale. Method: this quantitative, prospective study investigate 56 people with ostomy at the late postoperative stage using a semi-structured questionnaire. The data were analyzed using nonparametric statistical tests. Results: 58.9% of participants were 54 to 69 years old, 41% had completed elementary school, 53.6% were married, 66% retired and 71.4% colostomized. The complications affecting 48.2% included dermatitis in 19.6%. On the adaptation scale, the overall average was 144.7. The highest scoring dimensions were self-care (18.8) and self-concept (42.5); and lowest, sexual interaction (15.1). The social/religious support domain was found to differ significantly between groups (p = 0.031). Conclusion: a significant part of the study population had complications and was less adapted to the ostomy. Early assessment can be a strategy for preventing complications.